GENERAL ASPECTS OF THE MONITORING OF REGIONAL SOCIAL AND ECONOMIC DEVELOPMENT - Svetlana R. Khaltaeva (Статистика и экономика, 2016)
The article describes theoretical and practical aspects of the organization monitoring system of socio-economic development in the region, considers the organization of a regional monitoring on the basis of the analysis of the indicators of socio-economic development of the Republic of Buryatia. Also the Russian regions experience in the organization and functioning of the regional socio-economic development monitoring system is given.